Implementasi Sistem Pendukung Keputusan Menentukan Warga Penerima Kartu Indonesia Sehat (KIS) dengan Menerapkan Metode Analitycal Hierarcy Process Berbasis Web Studi Kasus Kelurahan Balai Gadang Kecamatan Koto Tangah Padang - Taufik Nur Zam Zam; Yuhandri Yunus; Harkamsyah Andrianof (LPPM Politeknik Jambi, 2023)
The Healthy Indonesia Cards (KIS) is an identity card for National Health Insurance (JKN) participants managed by BPJS Kesehatan. This Healthy Indonesia Card is different from BPJS. The difference is that the Healthy Indonesia Card is only specifically for people with an underprivileged economy and the poor, while BPJS Health targets all Indonesian people, regardless of community background. The Healthy Indonesia Card (KIS) itself is a program that the Indonesian people feel the most benefit from, because people can get treatment without spending money. Sub-districts can also help get letters to get Healthy Indonesia Cards, but in issuing letters proposing names of residents who are eligible to get Healthy Indonesia Cards (KIS) are not as optimal as Balai Gadang Village, for this a decision support system (SPK) is needed. The decision support system in this study uses the Analytical Hierarchy Process (AHP) method. The Analytical Hierarchy Process (AHP) method was chosen because it can be used in solving complex unstructured situations for components in a hierarchical arrangement, by selecting which variable has the highest priority to influence the outcome of that situation. A system created using the PHP programming language and MySQL database that can help the Balai Gadang sub-district select residents in a timely and accurate manner.